2014
DOI: 10.1159/000365248
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex as Moderators of the Placebo Response - An Evaluation of Systematic Reviews and Meta-Analyses across Medicine

Abstract: Predictors of the placebo response (PR) in randomized controlled trials (RCT) have been searched for ever since RCT have become the standard for testing novel therapies and age and gender are routinely documented data in all trials irrespective of the drug tested, its indication, and the primary and secondary end points chosen. To evaluate whether age and gender have been found to be reliable predictors of the PR across medical subspecialties, we extracted 75 systematic reviews, meta-analyses, and meta-regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 109 publications
10
71
4
Order By: Relevance
“…Among the patient characteristics frequently accused of driving the placebo response are sex (with larger placebo responses in women) and (younger) age. Although these factors were shown to be relevant in some trials (Thijs et al, 1990;Freeman and Rickels, 1999;Rheims et al, 2008;Cohen et al, 2010;Yildiz et al, 2011;Agid et al, 2013;Arakawa et al, 2015), a recent review (Weimer et al, 2015a) of 75 systematic reviews and metaanalyses including more than 1500 trials, 150,000 patients, and 40 medical indications revealed that age and sex were not significant predictors of placebo responses in RCT, despite occasional evidence from experimental research (Aslaksen et al, 2007;Weimer et al, 2013b).…”
Section: B Influence Of Patient Characteristicsmentioning
confidence: 99%
“…Among the patient characteristics frequently accused of driving the placebo response are sex (with larger placebo responses in women) and (younger) age. Although these factors were shown to be relevant in some trials (Thijs et al, 1990;Freeman and Rickels, 1999;Rheims et al, 2008;Cohen et al, 2010;Yildiz et al, 2011;Agid et al, 2013;Arakawa et al, 2015), a recent review (Weimer et al, 2015a) of 75 systematic reviews and metaanalyses including more than 1500 trials, 150,000 patients, and 40 medical indications revealed that age and sex were not significant predictors of placebo responses in RCT, despite occasional evidence from experimental research (Aslaksen et al, 2007;Weimer et al, 2013b).…”
Section: B Influence Of Patient Characteristicsmentioning
confidence: 99%
“…19 Similarly, a high number of study visits by patients with IBD 18,20 is associated with increased placebo response rates and indicates that one of the driving factors for the placebo response is the frequency of doctor-patient interactions. 21 The reason(s) why European trials or trials with European centre participation, generate higher placebo responses in patients with ulcerative colitis 22 than trials without European involvement remains uncertain.…”
Section: Ibdmentioning
confidence: 99%
“…5 In a review of the placebo response across many medical conditions, 19 no evidence was found that sex contributes to the placebo response despite occasional reports from experimental settings suggesting otherwise, 65 and only marginal evidence that age might have a role, with younger adult patients exhibiting larger placebo response rates than older adults. This larger placebo response rate was the case in one of the IBS meta-analyses, 24 but it has also been noted that children with functional gastrointestinal diseases in general might exhibit larger placebo responses in RCTs than adolescents and adults, 116 similar to findings in attention deficit hyperactivity disorder and depression.…”
Section: Nauseamentioning
confidence: 99%
“…In each phase, the groups were compared by calculating difference scores between pain with and without the 'TENS' device activated (difference = pain with TENS -pain without TENS; positive scores indicated nocebo hyperalgesia) that were analysed via mixed ANCOVAs with group and trial as factors, controlling for age and gender. Age and gender were included as covariates as both have been found to influence pain perception in general [21,38] as well as the placebo effect specifically [37]. However, the pattern of results were identical without these covariates included in the model.…”
Section: Data Handling and Analysismentioning
confidence: 99%